A noite tem mais luzes: considerações sobre a representação do desejo lésbico no romance de Cassandra Rios - Paim, Mariana Souza (2014)
This study analyzes representations of female homosexuality in the novel A noite tem mais luzes (1968), authored by Cassandra Rios, a writer from São Paulo. Cassandra‘s literary production is permeated by the lesbian theme‘s existence being considered one of the first Brazilian writers to ensure the existence of gay characters as protagonists of her novels. Her work is thus a natural source for us understanding the female homosexual desire‘s exposure on Brazilian 1960s. In this meanline, we follow the protagonist‘s path Pascale, analyzing lesbian identity that is problematic by character, so we seek to establish a dialogue between theoretical texts and narrative scenes that expose the discourses on lesbian identity in the novel. Here also are investigating whether they are experienced and constructed gender roles perceived as sexually "deviant" on a quest to understanding gender relations‘ dynamics that underlie these constructs. We seek to further understand what are these subjects‘ circulation spaces and experiences. The analysis' perspective allows us to place this research in the field of post-structuralist studies, being referenced by theorists like Michel Foucault (1967; 1996; 2012); Judith Butler (2014); Stuart Hall (2003; 2006), among other authors who study identity‘s questions. From this work‘s analysis we can see the constant changes and mechanisms that underlie identification and visibility‘s game, highlighting the conflicts and subjective process such questions and showing it, mainly as a historical building.